Hydrogen Sulfide Is a Novel Regulator of Bone Formation Implicated in the Bone Loss Induced by Estrogen Deficiency - Grassi, Francesco (J Bone Miner Res, 2015)
Hydrogen sulfide (H(2)S) is a gasotransmitter known to regulate bone formation and bone mass in unperturbed mice. However, it is presently unknown whether H(2)S plays a role in pathologic bone loss. Here we show that ovariectomy (ovx), a model of postmenopausal bone loss, decreases serum H(2)S levels and the bone marrow (BM) levels of two key H(2)S-generating enzymes, cystathione β-synthase (CBS) and cystathione γ-lyase (CSE). Treatment with the H(2)S-donor GYY4137 (GYY) normalizes serum H(2)S in ovx mice, increases bone formation, and completely prevents the loss of trabecular bone induced by ovx. Mechanistic studies revealed that GYY increases murine osteoblastogenesis by activating Wnt signaling through increased production of the Wnt ligands Wnt16, Wnt2b, Wnt6, and Wnt10b in the BM. Moreover, in vitro treatment with 17β-estradiol upregulates the expression of CBS and CSE in human BM stromal cells (hSCs), whereas an H(2)S-releasing drug induces osteogenic differentiation of hSCs. In summary, regulation of H(2)S levels is a novel mechanism by which estrogen stimulates osteoblastogenesis and bone formation in mice and human cells. Blunted production of H(2)S contributes to ovx-induced bone loss in mice by limiting the compensatory increase in bone formation elicited by ovx. Restoration of H(2)S levels is a potential novel therapeutic approach for postmenopausal osteoporosis.